A Classification Framework for Exploring Technology-Enabled Practice–FrameTEP. (December 2016) - Prestridge, Sarah; de Aldama, Carlos
This article theorizes the construction of a classification framework to explore teachers' beliefs and pedagogical practices for the use of digital technologies in the classroom. There are currently many individual schemas and models that represent both developmental and divergent concepts associated with technology-enabled practice. This article draws from a depth of literature in this field to synthesize a classification framework used as an analytic tool to interpret technology-enabled practice. The framework was drawn from literature covering teachers' epistemic beliefs, pedagogical beliefs, pedagogical approaches, technological competency, and perceived levels of learning. It emerged as a result of the need to analysis case study data from a large-scale research project into the effective use of digital games in the classroom: Serious Play: Digital Games, Learning and Literacy for Twenty First Century Schooling . Yin suggests the use of a uniform framework to enable cross-case synthesis. The framework provides an analytical tool to help interpret why and how teachers are using, in this case, digital games in their classrooms. It also provides a significant contribution to the variances in technology-enabled practice along the traditional-constructivist continuum as well as to the relationship in how teacher beliefs direct pedagogical practice and choice of technologies used for learning.